Stormrage - Knaak, Richard A. (World of WarCraft., 2010)
Malfurion Stormrage, the leader of the night elf druids, returns to the spirit world of the Emerald Dream hoping to replenish his powers after the Second Invasion and becomes trapped within the dream, battling to escape and save his people.